ANALISIS EKIVALENSI SEPEDA MOTOR DENGAN METODE REGRESI LINIER BASIS KECEPATAN DI KUTA UTARA SAAT PPKM - I Made Kariyana; Gede Sumarda; Yoga Andika; Tri Hayatining Pamungkas (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
The use of motorcycle modes in Badung Regency has the highest population compared to other modes of transportation. The congestion on the Badung City Highway is a result of the growth rate of motorcycles, as is known that the 1997 Indonesian Road Capacity Manual, which is used to assess traffic performance in Indonesia as a whole, still uses the equivalence of passenger cars as a basis. Based on this context, a study was conducted on motorcycle equivalence analysis using a speed-based linear regression method and compared the results with the equivalence of passenger cars in the 1997 Indonesian Road Capacity Manual, which was carried out during the conditions of the implementation of restrictions on community activities, especially on Canggu Highway, Kerobokan Highway, and Padang Luwih Highway. The method applied in this study is quantitative, namely by calculating the equivalence of a motorcycle with regression analysis. The research analysis showed that the equivalence of motorcycles, light vehicles, and heavy vehicles in Kerobokan highway are 1.00, 8.36, and 16.22, respectively. The equivalence value in the Canggu Highway for motorcycles, light vehicles, and heavy vehicles are 1.00, 7.15, and 15.28, respectively. Padang Luwih Highway gets a motorcycle equivalence of 1.00, for light vehicles 3.98, and for heavy vehicles 14.53. Meanwhile, the performance figures obtained on Canggu Highway were 9,059 ssm/hour with a saturation degree of 3.46. On Kerobokan Highway, the degree of saturation is 2.56 ssm/hour, with a traffic flow of 6.925 ssm/hour. Meanwhile, the traffic flow data for the Padang Luwih Highway section is 9,008 ssm/ hour with a saturation degree of 2.93 ssm/hour.